Difficulties of Vietnamese Students in Learning Academic Writing - Ngo Phan Anh Nghi; Trong Nhan Truong (International Journal of Asian Education, 2023)
Writing is consistently regarded as one of the most challenging language-learning abilities. This paper investigates the challenges Vietnamese students face in learning academic writing in English. Ninety-five students from grades 6 to 12 who have been studying English for several years were surveyed using a questionnaire. The questionnaire comprised 14 Likert-scale statements and one multiple-choice question to determine their interests, habits, and perspectives toward learning English. Most participants expressed a keen interest in learning languages but felt that their writing skills in English were not up to par, attributing this to inadequate time spent practicing. As a result, it is suggested that secondary school students in Vietnam increase their writing practice time in English and alter their learning routines and habits accordingly.